Optimasi Waktu Kalsinasi Karbon Aktif dari Bunga Cemara Laut (Casuarina equisetifolia) dalam Kombinasi dengan Bleaching Earth untuk Pemurnian Minyak Jelantah - Fadila, Radhiatul; Nizar, Umar Kalmar (Lembaga Yasin AlSys, 2025)
Used cooking oil is a byproduct of repeated frying processes that undergoes quality degradation due to continuous oxidation and heating, resulting in harmful compounds such as free fatty acids, peroxides, and polymers. This study aims to evaluate the effectiveness of purifying used cooking oil using a combination of two adsorbents: activated carbon derived from Casuarina equisetifolia (beach she-oak) flowers activated with NaOH, and bleaching earth. Activated carbon was synthesized through calcination at varying durations of 45, 60, 75, and 90 minutes to determine the optimal condition. The oil quality was evaluated by measuring acid number, saponification value, density, moisture content, and functional group analysis using infrared spectroscopy (FTIR). The results indicate that activated carbon calcined for 60 minutes produced the best outcomes, reducing the acid number from 14.92 to 5.07 mg KOH/g, increasing the saponification value to 43.33 mg KOH/g, achieving a density of 0.8693 g/mL in accordance with national standards (SNI), and reducing moisture content to 0.4330%. FTIR analysis showed decreased intensity in carbonyl groups and the disappearance of hydroxyl groups, indicating effective removal of polarized and oxidized compounds. These findings demonstrate that the combination of activated carbon from Casuarina equisetifolia flowers and bleaching earth is an effective and environmentally friendly purification method, supporting the sustainable use of biomass waste as adsorbent material.